2007
DOI: 10.1186/cc5904
|View full text |Cite
|
Sign up to set email alerts
|

The metabolic and renal effects of adrenaline and milrinone in patients with myocardial dysfunction after coronary artery bypass grafting

Abstract: IntroductionMyocardial dysfunction necessitating inotropic support is a typical complication after on-pump cardiac surgery. This prospective, randomized pilot study analyzes the metabolic and renal effects of the inotropes adrenaline and milrinone in patients needing inotropic support after coronary artery bypass grafting (CABG).MethodsDuring an 18-month period, 251 patients were screened for low cardiac output upon intensive care unit (ICU) admission after elective, isolated CABG surgery. Patients presenting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 32 publications
2
27
1
Order By: Relevance
“…In adults, an increase in arterial lactate and glucose concentration is a well‐known consequence to intravenous adrenaline infusion. This has been demonstrated in both healthy volunteers and in patients in shock of various aetiologies including cardiogenic shock and after cardiac surgery . In agreement with our results, previous studies demonstrated no change in the arterial lactate concentration by administration of intravenous dobutamine or dopamine in adult healthy volunteers and patients .…”
Section: Discussionsupporting
confidence: 93%
“…In adults, an increase in arterial lactate and glucose concentration is a well‐known consequence to intravenous adrenaline infusion. This has been demonstrated in both healthy volunteers and in patients in shock of various aetiologies including cardiogenic shock and after cardiac surgery . In agreement with our results, previous studies demonstrated no change in the arterial lactate concentration by administration of intravenous dobutamine or dopamine in adult healthy volunteers and patients .…”
Section: Discussionsupporting
confidence: 93%
“…There are no statistical differences in early outcomes as reported by others [17,18] although there is a tendency of longer ICU and LOS in Group 2 pts.…”
Section: Commentscontrasting
confidence: 45%
“…Epinephrine administration to septic patients also has been found to increase blood LPR, a result speculated-without further investigation-to be associated with a lack of sufficient oxygen delivery [100]. However, nonseptic patients infused with epinephrine at clinically relevant doses also have exhibited elevated LPR [101][102][103]. Finally, the b2-adrenergic agonist ritodrine has been associated with increased blood LPR in pregnant women during labor [104].…”
Section: Catecholaminesmentioning
confidence: 99%